(untitled) (EAAE Annual Conference Proceedings, 2023)
Literally translated ‘Bauhaus’ means ‘Build house’. The notion seems to resonate the often uncritical attitude of educational programs in architecture and urbanism towards greenfield development. To be honest, the number of assignments that challenge students to design something new on pristine land still overwhelms the number of questions that ask them to think about an architecture that goes along with reclaiming open space. As the European Commission has set the ambition in 2015 to evolve for all member states to a situation of no net land take in 2050, it is time for architecture schools to reset their ambitions too.